Framework development of bills of quantities accuracy in construction organisation - Bandi, Shamsulhadi (2015)
The Bill of Quantities (BQ) is a document that itemises information collected from the process of measurement and provides the descriptions, quantities and information of items required in a contract. These information are mainly used by contracting organisations in fulfilling their contractual duties. However, previous studies have revealed some concerns on the information contents of the BQ that have impacted its usability by contractors. Attempts to improve the BQ seem to concentrate on the BQ formats that do not parallel the improvements required for the BQ. This research aims to develop a conceptual framework that indicates important information requirements and significant issues as the basis to improve the uses of the BQ. The research outlines five objectives which include determining the uses of the BQ to the contracting organisations, determining the important BQ information requirements, determining significant issues impeding the uses of the BQ, developing and validating a conceptual framework as the basis to improve the uses of the BQ. Through survey, questionnaires were distributed to 500 active G7 contractors in Kuala Lumpur where 22.4% responded. Data was tested and analysed by means of Communality, Cronbach's Alpha, Relative Importance Index and the Analysis of Importance. The research determines 30 uses of the BQ, and shows that quantities is the most important information required in the overall uses of the BQ while inaccurate/wrong quantities, insufficient information on quantities, and inaccurate descriptions are the most significant issues impeding the uses of the BQ. The information requirements and issues that were considered important from the analyses are the main inputs to the framework. These are organised into two levels of importance, with inputs featured in the first level have higher weightage in improving the respective uses of the BQ as compared to the inputs featured in the second level of the framework. The framework asserts that improving the respective uses of the BQ can be planned in two stages based on the respective levels of importance. Validation for the framework was carried out through interviews with 10 personnel with at least 15 years of construction related experience. The results show an acceptable congruity where no changes are required, affirming the validity of the framework. The framework provides a usable basis in strategising improvements on the uses of the BQ to the contracting organisations.